Efforts to Improve Economic Literacy in Students of Kalam Kudus Christian High School in Welcoming the Era of Society 5.0 - Siagian, Lasma; Sihombing, Sarina; Nababan, Netty Winda Sari (Fakultas Ilmu Komputer, Universitas Katolik Santo Thomas Medan, 2025)
This community service initiative focuses on improving economic literacy among students of SMA Kristen Kalam Kudus as preparation for facing challenges and opportunities in the era of Society 5.0. Society 5.0, a concept that emphasizes the integration of advanced technology with social systems, demands a workforce that is not only skilled in technology but also economically literate. This program aims to equip students with essential economic knowledge and skills, as well as enhance their understanding of financial concepts, entrepreneurship, and the digital economy. Through workshops, interactive discussions, and practical applications, this initiative provides students with the tools they need to navigate and succeed in an increasingly digital and connected world. This effort contributes to shaping a generation that is able to make informed economic decisions, thus supporting their personal and professional development in the context of Society 5.0.